If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -59 + 3x = 2x + 21 Reorder the terms: -59 + 3x = 21 + 2x Solving -59 + 3x = 21 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -59 + 3x + -2x = 21 + 2x + -2x Combine like terms: 3x + -2x = 1x -59 + 1x = 21 + 2x + -2x Combine like terms: 2x + -2x = 0 -59 + 1x = 21 + 0 -59 + 1x = 21 Add '59' to each side of the equation. -59 + 59 + 1x = 21 + 59 Combine like terms: -59 + 59 = 0 0 + 1x = 21 + 59 1x = 21 + 59 Combine like terms: 21 + 59 = 80 1x = 80 Divide each side by '1'. x = 80 Simplifying x = 80
| 5(0)+y=20 | | -7(-5n-2)=119 | | 42=34+q | | Log(x-6)=2 | | -1+6y=14 | | 8(4)(7)-9(3)+4(4)= | | 7x+5=5x-5 | | 10010001001002030+3-10= | | 3x+5=-8(6-5x) | | 11x-47-x=103 | | 4v=8v+32 | | 10m+12n+5m+3n+35= | | 2x-42-7x=84 | | 5x+2(1.5)=10 | | 49-9x+5x=27 | | 10000000000000000000000000000+e= | | 12-7x+4x=27 | | x+7.8=3 | | 2(y+3)=a | | 5(-4)+2y=10 | | 3x+9x-83=73 | | 6.5x+3.5y=9.5 | | 5x+75=10x-5 | | a=2(y+3) | | 6x+4x-97=103 | | 12=5x-9-2x | | -4y-42-3y=5y | | 11x-118-x=38 | | 12x-6x-86=82 | | 6x-8x-22=24 | | f(x)=4x^2-4x-8 | | 58-5x+x=62 |